Representative Liberal Democracy: Models, Limits and Unaccomplished Promises (2006)
The text presents the thesis that modern representative democracy is structured around two great traditions of liberal thought: those that emphasize democracy as a countermajoritarian political system, which defend rights and political equality as equalit